Susceptibility of Culex quinquefasciatus, the Vector of Lymphatic Filariasis, to Few Conventional and Newer Insecticides in Different Parts of Rajasthan - Singh, Karam V; Bansal, S K (Annals of Arid Zone, 2016)
Studies on the current insecticide susceptibility status of Culex quillquefasciallls against few conventional insecticides, i.e., DOT and Dieldrin, and more potent ones, i.e., malathion, fcnitrothion, propoxur and permethrin, were carried out in three desert districts (Barmer, Jodhpur and Pali) and three non-desert districts (Ajmer, Kota and Udaipur) in Rajasthan. The results of the investigations revealed that this vector species was no longer susceptible to any of the tested insecticides. In desert districts, the species exhibited resistance to DOT, dieldrin and malathion (mortalities <80%) and intermediate resistance to fenitrothion, propoxur and permethrin (mortalities 80-98%). However, in non-desert districts, the species, besides resistance to DOT, dieldrin and malathion, had also developed resistance to propoxur (mortalities <80%), but it exhibited intermediate resistance to fenitrothion and permethrin (mortalities 80-98%).